2021
DOI: 10.1038/s41467-020-20302-0
|View full text |Cite
|
Sign up to set email alerts
|

Early-life-trauma triggers interferon-β resistance and neurodegeneration in a multiple sclerosis model via downregulated β1-adrenergic signaling

Abstract: Environmental triggers have important functions in multiple sclerosis (MS) susceptibility, phenotype, and trajectory. Exposure to early life trauma (ELT) has been associated with higher relapse rates in MS patients; however, the underlying mechanisms are not well-defined. Here we show ELT induces mechanistic and phenotypical alterations during experimental autoimmune encephalitis (EAE). ELT sustains downregulation of immune cell adrenergic receptors, which can be attributed to chronic norepinephrine circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…To examine whether ERα signaling alters disease phenotype, we determined sensitivity to IFNβ, a first‐line MS treatment, in female and male WT and ERα −/− EAE mice. Importantly, sensitivity to IFNβ has been previously used a proxy for EAE phenotype with preliminary relevance to human MS condition (Inoue et al , 2016; Khaw et al , 2021a). While IFNβ successfully prevented EAE‐induced motor paralysis in WT mice, it did not stop motor paralysis in female and male ERα −/− EAE mice (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether ERα signaling alters disease phenotype, we determined sensitivity to IFNβ, a first‐line MS treatment, in female and male WT and ERα −/− EAE mice. Importantly, sensitivity to IFNβ has been previously used a proxy for EAE phenotype with preliminary relevance to human MS condition (Inoue et al , 2016; Khaw et al , 2021a). While IFNβ successfully prevented EAE‐induced motor paralysis in WT mice, it did not stop motor paralysis in female and male ERα −/− EAE mice (Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
“…This makes EAE a very versatile system to use in disease phenotyping studies and in translational pharmacology. For instance, a murine EAE model with early‐life trauma displayed disease phenotypes that are clinically, immunologically, and pathologically distinct (Khaw et al , 2021a). Notably, several immune markers in the IFNβ‐resistant EAE model are reminiscent of ones seen in IFNβ‐resistant MS patients, suggesting a cross‐species similarity in immune cell profiles (Inoue et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 28 Psychological stress has been shown to disrupt the blood–brain barrier 29 and cause epigenetic changes that may increase the risk of neurodegenerative disorders, including MS. 30 Neonatal emotional and physical stress increased the susceptibility and severity of MS-like disease in mice, due to downregulation of adrenergic receptors in innate immune cells. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Still, the trend is opposite in the case of IFN-β, mostly increasing the expression of tyrosine hydroxylase ( Zaffaroni et al, 2008 ). It has been reported that triggers such as early life trauma are associated with higher relapse rates in multiple sclerosis patients, and β1-adrenergic receptor agonist abrogates such changes at least in the experimental model in mice ( Khaw et al, 2021 ). Th17-specific deficiency of tyrosine hydroxylase in mice does not significantly alter the EAE disease score compared to wild-type mice but shows increased neutrophil infiltration in the CNS tissues ( Yang et al, 2021 ).…”
Section: Clinical Role Of Epinephrine and Norepinephrine In Various D...mentioning
confidence: 99%